Characteristics of two different types of thunderstorms in summer over the Nagqu area in China - Yan, Zhitao; Zhou, Yunjun; Hui, Lei (Frontiers in Earth Science, 2022)
To investigate further the characteristics of thunderstorms on the Qinghai–Tibet plateau, a plateau vortex (PV) thunderstorm and a local thermoconvective (TC) thunderstorm over the Nagqu area are analyzed using cloud-radar, microwave-radiometer, and raindrop-spectrometer data, and their macrophysical and microphysical evolution characteristics are discussed in terms of thermodynamic processes, microphysical processes, and lightning activities. The results show the following. 1) The cloud layer was deeper in the PV thunderstorm, but the TC thunderstorm had stronger short-time updraft with radial velocity exceeding 10 m/s, and the warming from the strong updraft action and latent heat release from the hydromorphic phase change was about twice that of the PV thunderstorm. 2) The water vapor density increased significantly when the thunderstorm cloud passed, and the liquid water content in the middle and lower layers exceeded 4 g/m3. The maximum ice water content in the TC thunderstorm was twice bigger than that in the PV thunderstorm. The trends of raindrop number concentration and rain intensity of the PV thunderstorm were similar, and the average particle size of raindrops was smaller than that of the TC thunderstorm. 3) Both types of thunderstorms accounted for more than 90% of negative cloud-to-ground (CG) lightning, and the regions with black-body temperature (TBB) less than −40°C and a larger TBB gradient were more favorable for the occurrence of CG lightning. 4) Thermodynamic fields bring water vapor and lift for microphysical processes, and microphysical changes release latent heat to enhance the dynamic effects, which together promote the development of the lightning activities. The peak radial velocity and ice-phase particle concentration were more than 10 min ahead of the active peak of the CG lightning. This study reveals the macrophysical and microphysical evolution characteristics of different types of thunderstorms and provides a certain scientific basis for disaster prevention and mitigation regarding thunderstorms over the Nagqu area.